Clinical and Radiological Outcome of Vancouver B2 Fracture Treated With Open Reduction and Internal Fixation. A Multicenter Cohort Analysis. Issue 8 (11th August 2022) - Biberthaler, Peter; Pflüger, Patrick; Wurm, Markus; Hanschen, Marc; Kirchhoff, Chlodwig; Aderinto, Joseph; Whitwell, George; Giannoudis, Peter V.; Kanakaris, Nikolaos
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To determine whether open reduction and internal fixation (ORIF) of periprosthetic Vancouver B2 fractures can lead to successful fracture healing in selected patients, when attention is given to the surgical exposure and the creation of a balanced extramedullary construct. Design: Retrospective. Setting: Two Level-1 trauma centers in Germany and United Kingdom. Methods: Patients with a B2 fracture receiving solely ORIF using a polyaxial locking plate were included for analysis. Patients with other fracture types, or treated with other methods, or with follow-up less than 12 months were excluded. Clinical characteristics, including the Charlson index, the American Society for Anesthesiologists score, and their preinjury functional levels, were recorded. Main outcome measures were 1-year mortality, revision rate, and radiological healing according to the Beals–Tower criteria. Results: A total of 32 patients (mean age, 79 ± 12 years) were enrolled. Six patients died within the first year (1-year mortality: 19%), and 5 were unavailable for follow-up studies. The remaining 21 patients had a mean follow-up of 30 months. Of 21, 20 had an excellent/good result using the criteria of Beals–Tower. One patient required revision surgery due to loosening and secondary subsidence of the stem. Conclusion: ORIF can be offered to selected patients suffering from B2 fractures, especially if their functional demand is limited, and perioperative risk high for revision arthroplasty. In this challenging cohort of patients, ORIF was a safe and effective therapeutic option. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.